Campaign advertising, redistribution and the gap between incomes of rich and poor - Dan Usher (Queen's University, Department of Economics, 2011)
The effect of a widening of the distribution of income upon society's choice of the amount of redistribution is a balancing of two opposing forces: the increase in redistribution in response to the increased ratio of mean to median income and the decrease in response to the greater advertising advantage of the wealthier half of the population. One cannot say a priori which force predominates.
Keywords: D63; D83; H26; 330; Campaign Advertising; Redistribution; Income Distribution